Co-designing soft climate adaptation: citizen centred solutions across four European pilots - Jost, Francois; Verones, Anna; Nachtigall, Nefertari; Ellena, Marta; Moreno, Lucía; Bielsa, Judith; Englund, Mathilda; André, Karin; Swartling, Åsa Gerger; Witton, Rosie; Bharwani, Sukaina; Baulenas, Eulalia; et al. (Frontiers in Climate, 2026)
Climate change impacts in Europe are intensifying and disproportionately affecting vulnerable populations. While adaptation strategies increasingly acknowledge the value of public participation and citizen science, there remains a gap in inclusive, evidence-based approaches that engage diverse citizen groups in shaping soft adaptation measures. This study examines a staged co-creation process implemented across four pilot regions (Aragón, Dresden, Malmö, Rome). Using a structured, adaptable sequence (stakeholder mapping, inception workshops, target-group focus groups, and multi-stakeholder co-creation) it engaged youth, working populations, multicultural communities, and citizens experiencing vulnerabilities to generate locally relevant, feasible, and just solutions. Thereafter, a cross-case synthesis of outputs across pilots and target groups was conducted. Results from cross-case analysis showed that participants converged on a recurrent suite of four soft adaptation measure typologies across sites and target groups: (1) inclusive, barrier-free, multilingual risk communication via trusted intermediaries and with non-alarmist framing; (2) education and capacity-building, embedding climate hazard literacy in schools and community venues (often through hands-on/citizen-science activities); (3) workplace adaptations, shifting from individual coping to shared responsibility; and (4) accessible cooling and warning services (climate shelters, hydration points, participatory cooling maps, early-warning and tailored alerts). These typologies reappeared across sites and target groups, but participants also specified context-dependent design features shaped by local climatic, physical, socio-cultural, and institutional conditions. Regarding the process, three features enabled effective outcomes: continuity (to build trust and iterate), socio-culturally tailored formats, and facilitation that lowered participation barriers. Key constraints were time and resource limits, coordination and responsibility gaps, communication accessibility issues, and representation gaps. The approach offers a practical example of how co-created proposals can be linked to implementation pathways (clarifying actors, resources and likely barriers) and how transferable procedures, including engagement sequences and transparent prioritisation steps, may be adapted to existing institutional roles and processes. Embedding such citizen engagement processes in municipal policy and budget cycles, and supporting low-cost, distributed actions through schools, workplaces, housing associations and civic partners, suggests one possible route towards more equitable, actionable climate adaptation.